Preference, Attitude, Recognition and Knowledge of Fruits and Vegetables Intake Among Malay Children - Sha An Ali, Mashitah (Malays J Med Sci, 2020)
BACKGROUND: The low consumption of fruits and vegetables among children is a global challenge. Foods recognition, nutrition knowledge and attitude are factors that influence children’s dietary practices. This study aims to assess the preference, attitude, recognition and knowledge of fruits and vegetables intake among Malay children. METHODS: A cross-sectional study was conducted among Malay children from five primary schools in Kuala Lumpur using self-administered questionnaires. RESULTS: A total of 134 Malay children (70 males and 64 females) with a mean (SD) age of 10.3 (1.0) years were recruited. Majority of the children had a father (61.9%) and a mother (56.0%) with secondary school education and earned below RM3,900 (70.9%) per month. The most preferred fruits and vegetable were bananas (91.9%) and carrots (71.4%), while the most recognised was oranges (100.0%) and tomatoes (96.3%). The children demonstrated an overall moderate level of attitude, recognition and knowledge with mean (SD) scores of 70.3 (19.9), 76.8 (18.1) and 73.6 (17.5), respectively, towards fruits and vegetables intake. Majority of the children (53.0%) were not aware of the daily recommended servings of fruits and vegetables, while 40.0% of children expressed a low attitude towards eating a variety of fruits and vegetables. The willingness to try a new type of vegetables and consume more vegetables was lower (68.7%) compared to fruits (75.4%). CONCLUSION: The preferences and recognition of fruits were higher compared to vegetables among the children. The children demonstrated a moderate level of attitude, recognition and knowledge towards fruits and vegetables consumption. Efforts to educate children on the recommended number of servings per day and improve their acceptability of vegetables should be implemented to promote the increase in fruits and vegetables consumption among children.